Pengaruh Gaya Kepemimpinan Situasional dan Komunikasi Organisasi Terhadap Kinerja Karyawan (Studi Eksplanatif Kuantitatif Pada CV. Putra Nugraha Sentosa Mojosongo) - Syah, Muh. Addin, Budi Santoso, M.Si (2017)
Employee performance is an important factor of the company, since this aspect determines its success. Leadership styles can affect the performances of employees in all aspects, in which the employee's performance will have an impact in achieving the company's goals. In rapid time of changes, the most effective style can be used is situational leadership style, in which the leaders must be able to identify his style according to the situation and condition. Good nizational communication can enhance good relations between colleagues. Communication between leaders and subordinates regarding good communication from top to bottom, bottom to top, and the horizontal is an important factor in creating an effective organization. Situational leadership style and organizational communication when combined can produce a good performance for the company's employees. The purpose of this study was to determine the influence of situational leadership style and organizational communication oemployees performance at CV. Nugraha Putra Sentosa Mojosongo partially or simultaneously. The population of this study were 225 people with 45 respondents as samples, using random sampling techniques. The data analysis was conducted by using ultiple linear regression analysis. Results of this research found that the style of leadership and organizationalcommunication positive and significant effects either tiallyimultaneously influence employee performance, but the style of leadership and organizational communication affects only 27%, while 73% are influenced by other factors such as: organizational climate, motivation and organizational culture.